2011
DOI: 10.1534/genetics.111.130773
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Recombination and Sympatric Genome Diversification Driven by Frequency-Dependent Selection in Borrelia burgdorferi, the Lyme Disease Bacterium

Abstract: How genomic diversity within bacterial populations originates and is maintained in the presence of frequent recombination is a central problem in understanding bacterial evolution. Natural populations of Borrelia burgdorferi, the bacterial agent of Lyme disease, consist of diverse genomic groups co-infecting single individual vertebrate hosts and tick vectors. To understand mechanisms of sympatric genome differentiation in B. burgdorferi, we sequenced and compared 23 genomes representing major genomic groups i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(134 citation statements)
references
References 89 publications
4
128
2
Order By: Relevance
“…This is similar to the finding that the locations of important virulence factor-encoding genes, such as dbpA-dbpB, ospA-ospB, and ospC, are conserved in particular genome segments, even though sizes may be somewhat different due to genetic rearrangements, especially on the outer edges of the linear plasmids. Gene duplication followed by rearrangement and mutations appear to have resulted in the evolution and antigenic variation of a number of B. burgdorferi virulence factors and other proteins (4,28,43,62,82,97,109,110). Often, duplicated genes that encode functionally redundant proteins that exhibit overlapping roles are present in the same operon, with each protein demonstrating altered specificities for host cell factors.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the finding that the locations of important virulence factor-encoding genes, such as dbpA-dbpB, ospA-ospB, and ospC, are conserved in particular genome segments, even though sizes may be somewhat different due to genetic rearrangements, especially on the outer edges of the linear plasmids. Gene duplication followed by rearrangement and mutations appear to have resulted in the evolution and antigenic variation of a number of B. burgdorferi virulence factors and other proteins (4,28,43,62,82,97,109,110). Often, duplicated genes that encode functionally redundant proteins that exhibit overlapping roles are present in the same operon, with each protein demonstrating altered specificities for host cell factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination is known to maintain sequence polymorphisms within B. burgdorferi s.l. populations (Haven et al, 2011) and the high number of STs can impede the identification of associations with clinical manifestations of LB. The test for recombination (not shown) indicated that this is a frequent event even for chromosomal housekeeping genes, as other studies (Haven et al, 2011) have also revealed.…”
Section: Association With Disseminated/persistent Forms Of Lyme Borrementioning
confidence: 99%
“…The 5S (rrf)-23S (rrl) intergenic spacer region is a tandemly repeated sequence that is unique to B. burgdorferi sensu lato and has been used to differentiate and identify different isolates of Borrelia spirochetes in many different sample types including ticks (Postic et al, 1994;Humphrey et al, 2010), blood meal hosts (Chu et al, 2008) and patients (Postic et al, 1998;Rijpkema et al, 2009). This is in contrast with other markers such as the ospA or ospC genes are not ideal for phylogenetic analyses of inferences because of frequent recombination events (Haven et al, 2011). Previous studies from the northeastern or midwestern US have examined the genetic structure of B. burgdorferi with other genes and found limited genetic structure at a local scale but evidence of regional barriers to gene flow (Qiu et al, 2002;Humphrey et al, 2010).…”
Section: Introductionmentioning
confidence: 99%